Stratification and isotope separation in CP stars - Cowley, C. R. (2009)
We investigate the elemental and isotopic stratification in the atmospheres of selected chemically peculiar (CP) stars of the upper main sequence. Reconfiguration of the UV-Visual Echelle Spectrograph in 2004 has made it possible to examine all three lines of the CaII infrared (IR) triplet. Much of the material analysed was obtained in 2008. We support the claim of Ryabchikova, Kochukhov & Bagnulo (RKB) that the calcium isotopes have distinct stratification profiles for the stars 10 Aql, HR 1217 and HD 122970, with the heavy isotope concentrated towards the higher layers. Better observations are needed to learn the extent to which 40Ca dominates in the deepest layers of all or most CP stars that show the presence of 48Ca. There is little evidence for 40Ca in the spectra of some HgMn stars, and the infrared (IR) triplet in the magnetic star HD 101065 is well fit by pure 48Ca. In HR 5623 (HD 133792) and HD 217522, it is likely that the heavy isotope dominates, though models are possible where this is not the case. While elemental stratification is surely needed in many cases, we point out the importance of including adjustments in the assumed Teff and log(g) values, in attempts to model stratification. We recommend emphasis on profiles of the strongest lines, where the influence of stratification is most evident. Isotopic mixtures, involving the four stable calcium nuclides with masses between 40 and 48 are plausible, but are not emphasized.